2018
DOI: 10.1515/intag-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Gum arabic based composite edible coating on green chillies

Abstract: Green chillies were coated with a composite edible coating composed of gum arabic (5%), glycerol (1%), thyme oil (0.5%) and tween 80 (0.05%) to preserve the freshness and quality of green chillies and thus reduce the cost of preservation. In the present work, the chillies were coated with the composite edible coating using the dipping method with three dipping times (1, 3 and 5 min). The physicochemical parameters of the coated and control chillies stored at room temperature (28±2ºC) were evaluated at regular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 21 publications
(32 reference statements)
0
9
0
4
Order By: Relevance
“…Gum arabic is a polysaccharide coating widely used because of good film forming properties, unique emulsification, encapsulating properties and been classified as "generally recognized as safe" (GRAS) by the joint FAO/WHO Expert Committee on Food Additives [14]. Several studies have shown the beneficial effects of the use of gum arabic as an edible coating on green chillies [15], banana [16], tomato [17] and many others in delaying ripening processes, reducing weight loss and microbial growth. Methyl cellulose is polysaccharide derivative of cellulose esters used as the film forming material and formulation of edible coatings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gum arabic is a polysaccharide coating widely used because of good film forming properties, unique emulsification, encapsulating properties and been classified as "generally recognized as safe" (GRAS) by the joint FAO/WHO Expert Committee on Food Additives [14]. Several studies have shown the beneficial effects of the use of gum arabic as an edible coating on green chillies [15], banana [16], tomato [17] and many others in delaying ripening processes, reducing weight loss and microbial growth. Methyl cellulose is polysaccharide derivative of cellulose esters used as the film forming material and formulation of edible coatings.…”
Section: Introductionmentioning
confidence: 99%
“…When applied on food products, the major active component of TO, thymol, promotes ion leakage from cell membranes, thereby compromising membrane integrity of microorganisms and improves antioxidant system through stimulated biosynthesis of phenolic compounds [21,27]. Furthermore, Valiathan and Athmaselvi [15] demonstrated that TO (0.5%) enriched GA (5%) coatings reduced loss of weight, total soluble solids and colour of coated green chillies stored at 28 • C for 12 days. To our best knowledge, there are no studies reporting the application of GA and MC with or without TO on "Acco" pomegranate arils to preserve postharvest quality and extend shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…During the storage time, guava fruits changed colour from green to yellow of the fruit peel (Rehman et al, 2020), due to chlorophyll degradation or qualitative and quantitative alterations of green pigment into another pigment as resulting of enzyme activities such as chlorophyll oxidase and peroxidase (Valiathan and Athmaselvi, 2018).…”
Section: Total Chlorophyll Contentmentioning
confidence: 99%
“…Este comportamiento es similar a lo reportado por Valiathan & Athmaselvi (2018), quienes usaron un recubrimiento de goma arábiga sobre chiles serranos con diferentes tiempos de inmersión. Los valores de firmeza oscilan para el control entre 2.26 N y 0.85 N, y para los recubiertos entre 2.62 N y 1.46 N al inicio y al final de la prueba con un tiempo de inmersión de un minuto.…”
Section: Características Físicas Y Químicas De Los Papelesunclassified